ANALISIS PERILAKU TANGGUNG JAWAB DALAM PEMBELAJARAN KEWARGANEGARAAN KELAS V DI SD NEGERI 1 SEDYO MULYO - Ajeng Ayu Saputri; Ramanata Disurya; Tanzimah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The research was conducted with the aim of describing the analysis of responsible behavior in civics learning class V at SD Negeri 1 Sedyo Mulyo. This type of research used a qualitative approach. Methods of collecting data in this study using questionnaires, interviews, and documentation. The results of the analysis of responsible behavior in civics learning class V at SD Negeri 1 Sedyo Mulyo can be concluded that students experience difficulties in responsible behavior material. Attitudes that influence students' lack of responsible behavior based on indicators are students not submitting assignments on time, chatting during class hours, not participating in group work properly, not listening to the teacher when explaining. Keywords: Responsible Behavior, Citizenship Learning.